2018
DOI: 10.1038/s41558-018-0245-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of continental-scale intensification of hourly rainfall extremes

Abstract: Temperature scaling studies suggest that hourly rainfall magnitudes might increase beyond thermodynamic expectations with global warming 1,2,3 ; that is, above the Clausius-Clapeyron (CC) rate of ~6.5% °C -1 . However, there is limited evidence of such increases in long-term observations. Here, we calculate continental-average changes in the magnitude and frequency of extreme hourly and daily rainfall observations from Australia over 1990Australia over -2013Australia over and 1966Australia over -1989. Obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
172
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 230 publications
(187 citation statements)
references
References 33 publications
15
172
0
Order By: Relevance
“…Although some studies have found that more extreme precipitation events tend to be more sensitive to daily temperature variations than less extreme events in some regions (e.g., Lenderink et al, 2011;Lenderink & van Meijgaard, 2008;Wasko et al, 2016), it has recently been recognized that the sensitivity to day-to-day temperature changes represents only an aspect of the variation in precipitation extremes that is distinct from the response of extreme precipitation to long-term warming (Guerreiro et al, 2017;Zhang et al, 2017). Although some studies have found that more extreme precipitation events tend to be more sensitive to daily temperature variations than less extreme events in some regions (e.g., Lenderink et al, 2011;Lenderink & van Meijgaard, 2008;Wasko et al, 2016), it has recently been recognized that the sensitivity to day-to-day temperature changes represents only an aspect of the variation in precipitation extremes that is distinct from the response of extreme precipitation to long-term warming (Guerreiro et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have found that more extreme precipitation events tend to be more sensitive to daily temperature variations than less extreme events in some regions (e.g., Lenderink et al, 2011;Lenderink & van Meijgaard, 2008;Wasko et al, 2016), it has recently been recognized that the sensitivity to day-to-day temperature changes represents only an aspect of the variation in precipitation extremes that is distinct from the response of extreme precipitation to long-term warming (Guerreiro et al, 2017;Zhang et al, 2017). Although some studies have found that more extreme precipitation events tend to be more sensitive to daily temperature variations than less extreme events in some regions (e.g., Lenderink et al, 2011;Lenderink & van Meijgaard, 2008;Wasko et al, 2016), it has recently been recognized that the sensitivity to day-to-day temperature changes represents only an aspect of the variation in precipitation extremes that is distinct from the response of extreme precipitation to long-term warming (Guerreiro et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Using the Clausius‐Clapeyron relation to predict precipitation extremes is considered a better approach than using mean precipitation changes (Allen & Ingram, ; Emori & Brown, ). However, precipitation extremes scaling with temperature change can be different among various timescales of precipitation accumulation (Guerreiro et al, ), as well as among different regions (Kharin et al, ) mainly due to different changes in dynamics (Pfahl et al, ). Most of these studies focused on fixed‐duration (e.g., hourly or 1 day) precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Some gridded 10.1029/2019GL083371 interpolated rainfall products are indeed available for free (e.g., Donat et al, 2013aDonat et al, , 2013b; however, various authors warn on the validity of results obtained using these products for analyzing extreme rainfall amounts, especially in areas with complex orography (King et al, 2013;Libertino et al, 2016). The shortage of studies on the short-duration extremes is then a remarkable issue, considering that it is not possible to directly downscale conclusions from daily data analyses, due do the different generating mechanisms of extreme rainfall at different time scales (Barbero et al, 2017;Guerreiro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%